A wavelet‐based approach for describing the mechanical behaviour of cellular beams. Issue 1 (7th December 2020) - Rajana, Komal; Alonso‐Rodríguez, Andrés; Tsavdaridis, Konstantinos Daniel
Abstract: This paper describes how a wavelet model comprised of a linear combination of sine terms is capable of representing the cross‐section inertia variation along the length of cellular beams. This allows the efficient computation of deflections of cellular beams when these are deployed as a part of steel‐concrete composite flooring systems. This method does not involve purely statistical approaches or piece‐wise integration of moment‐curvature relationships that lead to cumbersome matrix approaches and complicate the assessment of deflections. Despite its simplicity, the proposed approach is found to be reliable as it successfully predicts displacements obtained through finite element model representations of more than 260 cases with errors smaller than ±5 %. Furthermore, the proposed analytical description of cross‐section inertia along the beam length is defined by only three parameters that can be inferred through linear expressions considering the geometrical characteristics of a perforated beam, namely, the ratio of flange to web thickness, the second moment of inertia of the steel beam and the ratio between beam length and depth, making it easy for widespread application by practitioners.